Making sense of Prato: a case study in migration studies and global economic restructuring through the lens of two recent books - Barberis , Eduardo (Cambio. Rivista sulle Trasformazioni Sociali, 2020)
A book review of Elizabeth L. Krause, Tight Knit: Global Families and the Social Life of Fast Fashion (University of Chicago Press, 2018) and Antonella Ceccagno, City Making and Global Lab our Regimes: Chinese Immigrants and Italy’s Fast Fashion Industry (Palgrave Macmillan, 2017).